2010
DOI: 10.1128/jvi.01911-09
|View full text |Cite
|
Sign up to set email alerts
|

Polyubiquitination of APOBEC3G Is Essential for Its Degradation by HIV-1 Vif

Abstract: Proteasomal degradation of APOBEC3G is a critical step for human immunodeficiency virus type 1 (HIV-1) replication. However, the necessity for polyubiquitination of APOBEC3G in this process is still controversial. In this study, we showed that although macaque simian immunodeficiency virus (SIVmac) Vif is more stable than HIV-1 Vif in human cells, SIVmac Vif induces degradation of APBOEC3G as efficiently as HIV-1 Vif. Overexpression of APOBEC3G or lysine-free APOBEC3G stabilized HIV-1 Vif, indicating that APOB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
16
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 30 publications
(45 reference statements)
5
16
1
Order By: Relevance
“…1A, lanes 2, 4, and 6, respectively), although we transfected the same amount of Vif expression plasmid in each instance. This piece of data is consistent with our previous finding that increased expression of A3G will stabilize Vif protein expression (60).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…1A, lanes 2, 4, and 6, respectively), although we transfected the same amount of Vif expression plasmid in each instance. This piece of data is consistent with our previous finding that increased expression of A3G will stabilize Vif protein expression (60).…”
Section: Discussionsupporting
confidence: 82%
“…As briefly mentioned in the introduction, Iwatani et al showed that lysines 297, 301, 303, and 334 are critical for A3G degradation (31), as mutation of these four residues to arginines dramatically increased A3G stability. Although this observation contradicts our present data and previously published studies by us and the Zheng lab in which lysine-deficient A3G is still sensitive to Vif-induced degradation (19,60), it may be reasonable to speculate that lysines 297, 301, 303, and 334 and the N terminus of A3G are essential ubiquitin sites for Vif to induce A3G degradation. This discrepancy warrants further investigation.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…These results indicate that, despite the cross-species comparison, SIV Vif is still using the canonical poly-ubiquitination and proteasome degradation pathway to purge cells of human A3B. These results mirror prior studies on human A3G and A3F, where 20 and 19 lysines were simultaneously converted to arginine, and the K-less variants resisted Vif-mediated degradation (Albin et al, 2013; Dang et al, 2008; Shao et al, 2010). Since A3B may very well restrict the replication of other viruses, including HBV, HPV, and HTLV (Ahasan et al, 2015; Lucifora et al, 2014; Ooms et al, 2012; Starrett et al, 2016; Starrett et al, 2017; Verhalen et al, 2016; Vieira et al, 2014; Warren et al, 2015), it is likely that additional A3B counteraction strategies exist and that the functional K-free construct described here may be useful as a mechanistic probe.…”
Section: Discussionsupporting
confidence: 78%
“…3A). To date, there is no consensus on the necessity for polyubiquitination of Vif for A3G degradation (13,51). However, the notion that both hA3G and HIV Vif are ubiquitinated and degraded by the same E3, ElonginB/C-Cullin5, is generally accepted (13,16,31,43).…”
Section: Discussionmentioning
confidence: 99%